Association between elevated glycosylated hemoglobin and cognitive impairment in older Korean adults: 2009–2010 Ansan cohort of the Korean genome and epidemiology study - Kim, Jung Sook; Chun, Byung Chul; Lee, Kyoungho (Frontiers in Public Health, 2024)
Objective Cohort studies on the risk of cognitive impairment in the older population of S. Korea based on glycosylated hemoglobin (HbA1c) levels are exceedingly rare. This study aimed to analyze the association between HbA1c levels and cognitive impairment in older Korean adults without dementia. Methods We conducted a cross-sectional study using data from a community-based Ansan cohort (2009–2010), which was part of the Korea Genome Epidemiology Study. The study included 853 cohort participants aged ≥59 years living in Ansan city. Cognitive function was evaluated using the Korean version of the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA). The MMSE and MoCA scores were categorized into normal cognition (≥24 and ≥ 23, respectively) and cognitive impairment (≤23 and ≤ 22, respectively). Multiple logistic regression analysis was used to estimate the association between HbA1c levels and cognitive impairment, with adjustments for covariates. Results The mean age of the participants was 66 years, and 433 (50.8%) were female. Cognitive impairment was observed in 12.5 and 44.3% of participants, based on the MMSE and MoCA, respectively. Regarding the MMSE scores, HbA1c level was a risk factor for cognitive impairment in women. Compared to normal HbA1c (≤5.6%) levels, adjusted odds ratios of MMSE decline for HbA1c 5.7–6.4% and HbA1c ≥6.5% were high: 2.16 (95% confidence interval [CI] 1.04–4.49) and 2.96 (95% CI, 1.04–8.39), respectively. Conclusion By improving glycemic control, the risk of cognitive impairment in the older population can be reduced. Further research on the role of sex differences in cognitive impairment is needed.